Perancangan Bangunan Menara Air pada Sistem Sea Water Reverse Osmosis - Imanto, Frenki; Wilujeng, Auliana; Fatah, Misbakhul; Hamid, Abdul; Wijaya, Septian (Indonesian Society of Applied Science, 2024)
Water tower buildings using the SWRO (Sea Water Reverse Osmosis) system are needed as part of processing sea water into clean water. So that it can be used by the local community to meet their daily needs. In this research we designed a water building in the SWRO system by analyzing it using the FEM method. The upper frame is made from gray cast ATM A48 material with grade 25 with a C channel type profile measuring 80x8 mm. Meanwhile, the supporting frame is made of gray cast ATM A48 material with grade 25 with an L type profile with dimensions of 40x40x3 mm and 30x30x3 mm. The largest stress load stimulation was obtained at 415.8 MPa on the upper frame, which indicates it is in the safe category. Meanwhile, the largest displacement value was 60.46 mm for the upper frame. This shows that the design of water structures in the SWRO system in this research can be classified as safe.